2015
DOI: 10.1158/0008-5472.can-15-0614
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Activation Promotes Keratinocyte Survival during Early Skin Carcinogenesis via Metabolic Alterations

Abstract: Pharmacologic activation of the transcription factor NRF2 has been suggested to offer a strategy for cancer prevention. In this study, we present evidence from murine tumorigenesis experiments suggesting there may be limitations to this possibility, based on tumorigenic effects of Nrf2 in murine keratinocytes that have not been described previously. In this setting, Nrf2 expression conferred metabolic alterations in keratinocytes that were protumorigenic in nature, affecting enzymes involved in glutathione bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 41 publications
(60 reference statements)
4
37
0
Order By: Relevance
“…In addition, we evaluated detoxification enzymes, some of which are regulated by Nrf2 in keratinocytes [39]. There were no significant differences in the expression levels of detoxification enzymes that are reportedly not regulated by Nrf2 between CD109 +/+ and CD109 −/− skins (Supplementary Figure S4A); however, the mRNA and protein levels of several detoxification enzymes that are reportedly regulated by Nrf2 [34, 40] were elevated in CD109 −/− skin compared with in CD109 +/+ skin (Supplementary Figure S4B and S4C). Moreover, microarray analysis revealed that Akr1c19, one of the Nrf2-related detoxification enzymes [40], was downregulated in CD109 +/+ skin and upregulated in CD109 −/− skin after DMBA treatment, as compared with untreated skin (Supplementary Tables S2 and S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we evaluated detoxification enzymes, some of which are regulated by Nrf2 in keratinocytes [39]. There were no significant differences in the expression levels of detoxification enzymes that are reportedly not regulated by Nrf2 between CD109 +/+ and CD109 −/− skins (Supplementary Figure S4A); however, the mRNA and protein levels of several detoxification enzymes that are reportedly regulated by Nrf2 [34, 40] were elevated in CD109 −/− skin compared with in CD109 +/+ skin (Supplementary Figure S4B and S4C). Moreover, microarray analysis revealed that Akr1c19, one of the Nrf2-related detoxification enzymes [40], was downregulated in CD109 +/+ skin and upregulated in CD109 −/− skin after DMBA treatment, as compared with untreated skin (Supplementary Tables S2 and S3).…”
Section: Resultsmentioning
confidence: 99%
“…The authors also detected Nrf2 and p21 expression in TGF-β-responding tumor cells at the tumor–stromal interface [31]. In addition, Nrf2-deficient mice were reported to be more susceptible to DMBA-induced skin tumorigenesis [33] and Nrf2 activation protected keratinocytes in the early phase of skin tumorigenesis [34]. These results are consistent with our data, suggesting that CD109 deficiency increases DMBA metabolism via the TGF-β/p21/Nrf2 pathway and resistance to DMBA-induced H- ras mutation in mouse keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, studies need to be conducted to determine the effects of chronic administration of pharmacologic agents such as WA. Furthermore, these are studies that have to be conducted for all Nrf2 inducers that move forward into clinical trials, regardless of their mechanisms of action, especially given the recent reports of Nrf2’s dual role in cancer [75] [76] [77]. …”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2 transgenic mice gradually developed severe chloracne-like lesions, which are highly reminiscent to the patients with chloracene/metabolizing acquired dioxin-induced skin hamartomas [45]. Furthermore, the Nrf2 activation promotes the human papilloma virus-induced or arsenite-induced carcinogenesis by upregulating the survival and proliferation of transformed keratinocytes [46,47]. These studies stress the importance of an appropriate balance between oxidative and antioxidative processes in maintaining epidermal homeostasis.…”
Section: Nuclear Factor-erythroid 2-related Factor-2 a Master Tramentioning
confidence: 99%